Antisipasi Peraturan Perpajakan Di Indonesia Terhadap Praktek Perpajakan Negara-Negara Tax Haven - Setiadi Alim Lim; Lilik Indrawati (Fakultas Ekonomi Universitas Katolik Darma Cendika, 2013)
To attract investors, some countries called tax haven countries have done unfair taxation practices. The practice of taxation by the tax haven countries encourage further growth in the activity of tax avoidance and tax evasion internationally. Almost all countries in the world are harmed by the practice of taxation of tax haven countries. The OECD has limited the practices unfair taxation of tax haven countries. Each country around the world will try to anticipate intensely the activity of tax avoidance and tax evasion through international cooperation and incorporate prevention efforts in taxation regulations. This paper will try to assess whether the provision of taxation in Indonesia has been able to anticipate the activities of international tax avoidance and tax evasion.